Use the expression to solve for the number.
2n + 4 = 22
2n = 22 - 4
2n = 18
n = 18/2
n = 9
The number is 9.
Hope this helps :)
Answer:
(x - 3) is a factor of P(x)
Step-by-step explanation:
if (x - 3) is a factor of P(x) then P(3) = 0
P(3) = 2(3)³ + 5(3)² - 28(3) - 15
= 2(27) + 5(9) - 84 - 15
= 54 + 45 - 99
= 99 - 99
= 0
since P(3) = 0 then (x - 3) is a factor of P(x)
S = n(a1 + an)/2
2S = n(a1 + an)
2S = na1 + nan
nan = 2S - na1
an = (2S - n a1)/n
Answer:i believe it is the first answer
Step-by-step explanation: